Attuning to the affective in literary tourism: Emotional states in Aberystwyth, Mon Amour. Issue 2 (16th April 2022) - Anderson, Jon; Smith, Kieron
Abstract: On a literary walking tour, many emotional 'states' are experienced by participants. These states have multiple causes, products and consequences, influenced in part by the socio-spatial identities of participants, their own imagined versions of the novel, and the material and cultural geographies of the tour itself. The Literary Atlas project sought to examine these emotional states by conducting literary walking tours based on English-language novels set in Wales. It attuned to the emotional states experienced by participants, in particular on a tour based around the locations cited in Malcolm Pryce's Aberystwyth Mon Amour. It did so to examine the ways in which these states cohere and collide to actively constitute the ongoing composition of the real-and-imagined worlds produced through this emergent literary geography. Attuning to the affects of the literary tour suggest that the strengths and persistence of these emotional attachments – to individual's own identities, imaginings and material places – come to define not only their place in the world, but also their world itself. As such, the ability of the participants to retain their cohesiveness as a group – however temporarily – in the face of difference and disagreement says much for their willingness to contextualise their own imaginings, and ultimately tolerate others', in a world of relational multiplicity.